KOMUNIKASI PEMBERDAYAAN MASYARAKAT MELALUI PENGELOLAAN DESA WISATA DI KABUPATEN KUNINGAN JAWA BARAT - Hidayati, Ratih Kurnia (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2023)
The purpose of this study is to see how the depiction of community empowerment communication construction through tourism management, namely tourism villages in the Kuningan Regency area of West Java using the literature study method. The concept of community empowerment, the concept of community participation, the concept of tourism management and the concept of tourism village management are used to describe the process of tourism village management in Kuningan Regency through community empowerment communication so as to encourage active role and community participation in tourism village management.